Background and common lesions in the female reproductive organs of giant anteaters (Myrmecophaga tridactyla) - de Moura, Fernanda Barthelson Carvalho [UNESP]; Lacerda, Zara Alves [UNESP]; Catão-Dias, José Luiz; Navas-Suárez, Pedro Enrique; Werther, Karin [UNESP]; Simões, Sarah Raquel Jesus Santos [UNESP]; Santos, Renato de Lima; Murillo, Daniel Felipe Barrantes; Watanabe, Tatiane Terumi Negrão; Fonseca-Alves, Carlos Eduardo; Rocha, Noeme Sousa [UNESP] (Frontiers, 2024)
The giant anteater (Myrmecophaga tridactyla) is a vulnerable species in South America and is considered endangered or near extinction in Central America. Therefore, studies describing the reproductive characteristics of this species are pivotal for its conservation. Thus, this study aimed to provide a morphological description of the female reproductive tissues of this species. We collected tissue samples from six female giant anteaters and performed gross, morphological, and histochemical analyses. Five adult subjects and one juvenile were included in the study. In the ovary, classifications were made according to the follicle and oocyte sizes: primordial, primary, secondary, early antral, or antral. Typical follicles with a single oocyte surrounded by a simple or stratified layer of cubic epithelium, atretic follicles, corpora lutea, corpora albicans, and ovarian cysts were also observed. No ovarian lesions were observed. By contrast, endometritis, metritis, mucometra, and endometrial cysts were identified in the uterus. Uterine alterations in these subjects were frequent and could affect reproduction.
Keywords: female; histopathology; morphology; reproduction; xenarthra